Research in Progress A cent'anni da Democrazia e Educazione di John Dewey - Beseghi, Emma (Il mestiere della pedagogia - Open Access, 2019)
The 100th anniversary of John Dewey's "Democracy and Education" was a valuable opportunity for the doctoral candidates of Pedagogical Sciences of the University of Bologna to observe some conceptual issues that emerge in the famous Deweyan work. They have identifyed four core themes, that were the subject of a seminar held in December 2016 at the Department of Educational Sciences "Giovanni Maria Bertin" and constitute the articulation of the four sections of this volume.